The exploration study on employability of Islamic banking and finance graduates from practitioners perspective - Azwan Abdullah; Mohd Khairy Kamarudin; Nor Azilawati Ahmad; Siti Syakirah Yusoh; Siti Fariha Muhamad; Mohammad Ismail (Intercontinental Management Research Review, 2015)
Islamic banking and finance industry in Malaysia have been emergence since l980s which provide facilities to the consumers such financing and deposit. Malaysian government is one of the components that make a lot of contribution to the Islamic banking and finance industry. One of the effort is recognized the higher education to conduct Islamic banking courses to meet the human capital for Islamic financial sector. However, job vacancies in Islamic banking sector still has a higher demand due to the shortageof qualified and skilled employees. Therefore, this study aimed to examine the employability skills that are required based on Islamic banking employers‟ perspective. This study employed semi-structured interviews with three experts from different position in industry, but they are specialize in the same field. This study indicated that employability of new graduates not only depend on academic achievement alone, but also required several skills to equip themselves with the market requirements. Fresh graduates should encounter themselves with a soft skills and practices in order to fulfil the vacancies that offered by Islamic banking sector.